A Manufacturing Strategy Utilizing a Continuous-Mode Reactor toward Homogeneous PEGylated Bioconjugate Production - Nakahara, Yuichi; Endo, Yuta; Takahashi, Kazutoshi; Kawaguchi, Tomoko; Kato, Keisuke; Matsuda, Yutaka; Nagaki, Aiichiro (Synthesis, 2023)
Protein PEGylation is a traditional bioconjugation technology that enhances the therapeutic efficacy and in vivo half-life of proteins by the formation of covalent bonds with highly activated ester group linked polyethylene glycol (PEG). However, the high reactivity of these reagents induces a random reaction with lysine residues on the protein surface, resulting in a heterogeneous mixture of PEGylated proteins. Moreover, the traditional batch-mode reaction has risks relating to scalability and aggregation. To overcome these risks of traditional batch-mode PEGylation, a manufacturing strategy utilizing structural analysis and a continuous-flow-mode reaction was examined. A solvent exposure analysis revealed the most reactive lysine of a protein, and the continuous-flow mode modified this lysine to achieve the mono-PEGylation of two different proteins within 2 seconds. This ultrarapid modification reaction can be applied to the gram-scale manufacturing of PEGylated bioconjugates without generating aggregates. A similar trend of the exposure level of protein lysine and mono-selectivity performed by continuous-flow PEGylation was observed, which indicated that this manufacturing strategy has the potential to be applied to the production of a wide variety of bioconjugates.
Keywords: continuous-flow synthesis; microreactor; PEGylation; cytokines; bioconjugates